2001
DOI: 10.1128/jb.183.11.3526-3530.2001
|View full text |Cite
|
Sign up to set email alerts
|

β-Ketoacyl Acyl Carrier Protein Synthase III (FabH) Is Essential for Fatty Acid Biosynthesis in Streptomyces coelicolor A3(2)

Abstract: The Streptomyces coelicolor fab (fatty acid biosynthesis) gene cluster (fabD-fabH-acpP-fabF) is cotranscribed to produce a leaderless mRNA transcript. One of these genes, fabH, encodes a ketoacyl synthase III that is essential to and is proposed to be responsible for initiation of fatty acid biosynthesis in S. coelicolor.Streptomyces spp. synthesize the majority of their fatty acids from branched starters such as isobutyryl, isovaleryl, and anteisovaleryl units to give odd-and even-numbered fatty acids with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…The fabH gene could be deleted only if a second copy of it was introduced into the cell. In this work and comparable experiments with E. coli, the additional copy of fabH was delivered as a chromosomal copy distant from its loci (11,16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabH gene could be deleted only if a second copy of it was introduced into the cell. In this work and comparable experiments with E. coli, the additional copy of fabH was delivered as a chromosomal copy distant from its loci (11,16).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, clear evidence has been obtained that FabH is an essential enzyme for fatty acid biosynthesis in E. coli, Streptomyces coelicolor, and Lactococcus lactis (11,16). In the cases of E. coli and S. coelicolor it was shown that the chromosomal fabH gene could be removed only if an additional copy of fabH was present; for S. coelicolor it was a second copy of the natural fabH gene (16), and in the case of E. coli it was the Salmonella enterica fabH (11). S. enterica is a close relative of E. coli, and it is known that the genes are fully interchangeable between the two species (11).…”
mentioning
confidence: 99%
“…In E. coli, FabH is subject to stringent feedback regulation by long-chain acyl-ACP so as to coordinate the rate of initiation with that of elongation (36). FabH is highly conserved, possessing an invariant triad of active site residues (28), as well as being essential across a diverse spectrum of both Gram-positive and Gram-negative bacteria that includes E. coli (47), Streptomyces coelicolor (67), and Lactococcus lactis (47). The uniqueness of the KASIII domain, conservation among FabH orthologs, and regulatory role in controlling FAS flux all suggest potential for broad-spectrum and bacterial selective inhibition.…”
Section: Trans-2-enoyl-acp (42 54) and Then Reduced To A Saturated mentioning
confidence: 99%
“…One of the essential enzymes, FabI, in the fatty acid biosynthetic pathway is a proven drug target with two marketed antibacterial agents, triclosan (antiseptic) and isoniazid (an anti-Mycobacterium tuberculosis agent) (12,13). The initiation condensing enzyme, FabH, and elongation condensing enzymes, FabF/B, are essential components of this biosynthetic pathway (14)(15)(16)(17) and consequently are highly conserved among key pathogens. Although no drugs targeting condensing enzymes are used in the clinic, two inhibitors, cerulenin (18) and thiolactomycin (19), with poor antibacterial activities were discovered more than two decades ago.…”
mentioning
confidence: 99%